Marketing de relacionamento: proposta de um plano de marketing de relacionamento para a Genyus Baterias - Monteiro, Marcos Cruz Walsh (2003)
The objective of this study is to propose a marketing relationship project to be used for Genyus Batteries in the construction of lasting relationships with relationship chain participants. To make it possible, concepts in the relationship marketing area are reviewed. Starting from the marketing plan suggested by Gordon (1999), was possible to verify wich strategies of this marketing plan were used or are being used by Genyus Batteries. The marketing plan used has eight phases: project for the project (O), client evaluation (1), 7 reference (2), enterprise evaluation (3), opportunities declaration (4), future state (5), business case (6) and change management and implementation (7); among these phases several relationship marketing strategies are analyzed to garantee their efficacy and to be certain the organization reaches its goals in the relationship formation and in the reach of differentiate position in the batteries market. It was certified that the studied organization doesn't have a relationship marketing project and, through this research, the organization will be able to use this plan in order to acquire efficacy in the relation marketing utilization.